Closeness, Conflict, and Culturally Inclusive Pedagogy: Finnish Pre- and In-service Early Education Teachers’ Perceptions - Yang, Wenwen; Laakkonen, Eero; Silvén, Maarit (Frontiers in Psychology, 2022)
This study explored the factorial and concurrent validity of a scale developed for assessing teachers’ self-efficacy beliefs in engaging with diversity in early childhood education settings. According to tests of measurement invariance, the conceptualization of the constructs varied to some extent between Finnish student teachers and qualified teachers. Qualified teachers reported, at the item level, higher confidence in engaging with diversity in mainstream early childhood classrooms than student teachers. Structural equation modeling demonstrated that for both groups, higher levels of reported confidence in planning and implementing inclusive teaching–learning interactions were related to a higher level of closeness during interactions with children. The evidence for concurrent validity may imply beneficial and reciprocal influences between teachers’ confidence in their professional competence and close teacher–child relationships. The implications of the study are discussed from the perspective of teacher training and professional development in the early childhood education context.